A omissão legislativa e as sentenças aditivas em sede de ação direta de inconstitucionalidade por omissão - Rosim, Arnaldo Ricardo (2011)
This essay is about the unconstitutional legislative omission due to constitutional patterns of limited efficacy and the search for their effectiveness. This work aims to reveal the trajectory of the Brazilian Supreme Court concerning the legislative omission through the two principal means of control listed on the Brazilian Constitution: the injunctive writand the direct unconstitutionality suit due to omission. It indicates the use of the additive sentences in order to supply the constitutionals omission by the Supreme Court, beginning with the injunctive writ. In addiction, it intends to analyse the possibility of this type of decision application in the direct unconstitutionality suit due to omission, considering also the principal objections listed by the doctrine for the application of this kind of defense in the Constitution